2018
DOI: 10.5194/acp-18-7539-2018
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene and monoterpene emissions in south-east Australia: comparison of a multi-layer canopy model with MEGAN and with atmospheric observations

Abstract: Abstract. One of the key challenges in atmospheric chemistry is to reduce the uncertainty of biogenic volatile organic compound (BVOC) emission estimates from vegetation to the atmosphere. In Australia, eucalypt trees are a primary source of biogenic emissions, but their contribution to Australian air sheds is poorly quantified. The Model of Emissions of Gases and Aerosols from Nature (MEGAN) has performed poorly against Australian isoprene and monoterpene observations. Finding reasons for the MEGAN discrepanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…CCAM uses the Australian land surface scheme, CABLE [64]. Biogenic emissions are provided by the Australian Biogenic Canopy and Grass Emissions Model (ABCGEM; [65]). Gas-phase chemistry is modelled using an extended version of the CB05 mechanism with updated toluene chemistry.…”
Section: Summary Of Chemical Transport Modelsmentioning
confidence: 99%
“…CCAM uses the Australian land surface scheme, CABLE [64]. Biogenic emissions are provided by the Australian Biogenic Canopy and Grass Emissions Model (ABCGEM; [65]). Gas-phase chemistry is modelled using an extended version of the CB05 mechanism with updated toluene chemistry.…”
Section: Summary Of Chemical Transport Modelsmentioning
confidence: 99%
“…The C-CTM is a modelling framework which simulates the emissions, transport and wet and dry deposition of chemical species in the atmosphere. Previously, the C-CTM has successfully been used in several air quality applications, including investigating smoke from biomass burning [33], shipping emissions [34] and biogenic emissions [35,36].…”
Section: Regional Air Quality Modelling Using C-ctmmentioning
confidence: 99%
“…The inventory specifies on-and off-road mobile, aircraft, shipping, commercial, domestic and industrial point sources at a resolution of 1 km. Natural biogenic emissions of isoprene and monoterpenes come from the Australian Biogenic Canopy and Grass Emissions Model (ABCGEM, [35]). Monoterpenes are treated as a lumped species.…”
Section: Regional Air Quality Modelling Using C-ctmmentioning
confidence: 99%
“…As biogenic emission is a major contribution to ozone formation, it is important for the model to account for it as accurately as possible. Emmerson et al [30] found that the Australian Biogenic Canopy and Grass Emission Model (ABCGEM), as implemented in the CCAM-CTM model used in this study, accounts for biogenic VOC emission (especially monoterpenes) from Australian eucalyptus vegetation better than the model of Emissions of Gases and Aerosols from Nature (MEGAN) when these modelled emissions are compared with observations.…”
Section: Discussionmentioning
confidence: 89%